Autoimmune encephalitis -- new awareness, challenging questions. - Irani, SR; Vincent, A (2011)
The field of autoimmune encephalopathies has expanded rapidly in the last few years. It is now well-established that a substantial proportion of encephalitides are associated with autoantibodies directed against the extracellular domains of cell-surface proteins which are critical in the regulation of neuronal excitability. These include LGI1, CASPR2, contactin-2 (VGKC-complex antibodies), and the NMDA, AMPA, and GABA(B) receptors. The clinical importance of these conditions lies in their frequent immunotherapy-response and, less commonly, their association with distinctive tumors. Studies which have examined cohorts of patients defined by these serum antibodies have identified a number of clinical features that have helped understand the core phenotypes of these conditions. In addition, sensitive antibody assays have allowed the expansion of the phenotypes to include a minority of patients with isolated epilepsies or psychoses. There is also evidence that autoimmune encephalitis may progress to adult-onset hippocampal sclerosis. Clinical, and accumulating scientific, data strongly suggest direct pathogenicity of these autoantibodies. The generation of the autoantibody, in some patients, can be explained by the presence of tumors which express their antigenic target. Serum antibody levels are higher than their levels in CSF in the vast majority of cases. However, the majority of patients do not harbor a tumor and the etiology of the disease in these patients is less clear. Below, we suggest models for the etiology and pathogenic mechanisms of these autoantibodies by incorporating concepts such as serum generation of the autoantibodies, the blood-brain barrier, intrathecal antibody production, and prodromal infections.